Which Approach is Preferred in Spinal Anesthesia: Median or Paramedian? Comparison of Early and Late Complications - Serpil Bayındır; Sibel Özcan; Fatma Koçyiğit; Onur Hanbeyoğlu (İstanbul Medical Journal, 2017)

(untitled)
Introduction: Spinal anesthesia is usually preferred for short-time surgery; the side effects of the process can show difference with techniques. We aimed to compare early and late complications of median and paramedian techniques in spinal anesthesia.Methods: Eighty patients with American Society of Anesthesiologists (ASA) I–III were allocated into the following two groups: Group M (median) and Group P (paramedian). Demographic data of the patients, ASA score, number of spinal anesthesia application, total surgery time, discharge time from the hospital, heart rate, mean arterial blood pressure, and early complications were recorded from the medical records of patients. Late complications of patients were learned by calling.Results: The number of applying spinal anesthesia number and the duration of anesthesia were longer in Group P than in Group M, and the difference was statistically significant (p<0.05). Fifty-two early complications and 23 late complications were observed. The common early complication (21%) was hypotension, and late complication (8.7%) was post-spinal headache (Group P, six patients; Group M, one patient); there was no difference between the groups.Conclusion: There was no significant difference in complications of spinal anesthesia applied via both technical approaches and discharge in short-continuance surgical cases. Although we defined a tendency for post-spinal headache in Group P, there was no statistically significant difference in our study.